Analyzing Student Performance in Learning English for General Academic Purposes (EGAP): A Comparative Action Research Study of Online and Offline Learning - Gufron, Gufron; Md Zamin, Ainul Azmin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This study aims to examine the impact of the pandemic on student performance in Learning English for General Academic Purposes (EGAP) through a comparative analysis of the pandemic and post-pandemic periods, using a Classroom Action Research (CAR) approach. The sudden shift to remote and hybrid learning during the pandemic required a transformation in education, prompting an investigation into its effects on students' English language proficiency. The research was conducted with a diverse sample of students across multiple disciplines. Quantitative and qualitative data were collected, including academic records, language proficiency tests, and observations. Results revealed significant differences in student performance between the two periods, highlighting the pandemic's impact on English learning outcomes. The study also explored various factors influencing these disparities, such as access to technology, learning environments, and adaptability to remote instruction. There is a gap in research on the long-term impact of the pandemic on EGAP performance across disciplines. The novelty of this study is its use of CAR to understand the ongoing effects and adaptive strategies in EGAP education. This research sheds light on the challenges students faced during and after the pandemic, the effectiveness of remote learning methods, and provides insights for educational policymakers and practitioners.